IMPLEMENTASI AKAD MURABAHAH PADA PRODUK PEMBIAYAAN MURABAHAH DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAITUL MAAL WAT TAMWIL FAJAR CABANG BEKASI - Sakum; Fitri, Ria Elsa (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
In the preparation of this thesis, researchers used qualitative research, the type of research used was library research and field research. Sources of data obtained through primary and secondary data sources, for data collection using two methods, namely: interviews and documentation, for data analysis techniques using 3 methods, namely data reduction, data presentation, and drawing conclusions. This study aims to determine the implementation or practice of the murabahah contract in murabahah financing products at Baitul Maal wat Tamwil Fajar Bekasi branch whether it is in accordance with Islamic law and Fatwa DSN MUI No. 04 / DSN-MUI / IV / 2000 About Murabaha. The result of this research is that in the practice of the murabahah contract at KSPPS BMT Fajar has implemented it according to the SOP and in accordance with Islamic law and fatwa DSN MUI No. 04 / DSN-MUI / IV / 2000 About Murabaha. Based on the results of the study, it can be concluded that the implementation of the murabahah contract on murabahah financing products at KSPPS BMT Fajar Bekasi branch is in accordance with Islamic law and Fatwa DSN MUI No. 04 / DSN-MUI / IV / 2000 About Murabaha. This is based on the results of the analysis of interviews with members who apply for murabahah financing.